Biological Therapeutic Treatment of Atopic Dermatitis - A. A. Kubanova; A. A. Kubanov; A. E. Karamova; D. V. Proshutinskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Atopic dermatitis is a chronic recurrent inflammatory disease caused, inter alia, by violations of the barrier function of the skin and pathological immune response in the form of an imbalance of Th1 and Th2 lymphocytes with increased production of IL-4, IL-5, IL-13, IL-31. Treatment of severe forms of atopic dermatitis is not an easy task due to the variability of the individual response to treatment, the short duration of the therapeutic effect and the frequent development of undesirable phenomena associated with the use of existing methods of systemic immunosuppressive therapy. The study of the pathogenesis of atopic dermatitis made it possible to identify the spectrum of molecular targets, providing the basis for researching alternative variants to the previously used systemic therapy methods - genetic engineering biological preparations. Contemporary data on the pathogenesis of atopic dermatitis as well as potential molecular targets for innovative biological preparations, the efficacy of which has been evaluated through clinical trials, are presented in the review.